Synthesis of ylidene derivatives of 4-amino-5-(4-tert-butylphenyl)-4H-1,2,4-triazole-3-thiol - I. I. Aksionova; O. I. Panasenko; E. G. Knysh (Zaporozhye State Medical University, 2015)
Aim. Modern medicine widely applies drugs from the group of 1,2,4-triazole (fluconazole, triazolam, alprazolam, letrozole and others) in the practice. This class of compounds has synthetic origin and a broad spectrum of biological activity, and is characterized by low toxicity. It is known that the presence of triazole ring in the molecule effects on the range and intensity of biological action. Methods and results. In order to create new biologically active compounds in a series of ylidene derivatives of 4-amino-5-(4-tretbutilfenil)-4H-1,2,4-triazole-3-thiol proposed preparative methods of synthesis 5-(4-tretbutilfenil) -4-R-4H-1,2,4-triazole-3-thiols have been proposed. The structure of synthesized compounds has been confirmed by 1H NMR-spectroscopy, chromatography-mass spectrometry and elemental analysis. Conclusion. This indicates the possibility of using these substances to further biological studies.